1999
DOI: 10.1021/ma9813587
|View full text |Cite
|
Sign up to set email alerts
|

Radical Ring-Opening Copolymerization of 2-Methylene 1,3-Dioxepane and Methyl Methacrylate:  Experiments Originally Designed To Probe the Origin of the Penultimate Unit Effect

Abstract: Pulsed-laser polymerization experiments were conducted on the copolymerization of 2-methylene 1,3-dioxepane (MDO) and methyl methacrylate (MMA) at 40 °C. Reactivity ratios, based on the terminal model, were determined from copolymer compositional analyses as r MDO = 0.057 and r MMA = 34.12. The average propagation rate coefficients, 〈k p〉, were determined for a number of feed compositions ranging from an MDO mole fraction of 0 to 0.916. It was not possible to obtain a 〈k p〉 value for the homopolymerization of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
63
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 36 publications
6
63
0
Order By: Relevance
“…9 Davis et al have reported copolymerization parameters for copolymerization of MDO with MMA at 40 C as r MDO ¼ 0:057 and r MMA ¼ 34:12 thereby showing the low tendency of cyclic ketene acetals to copolymerize with vinyl monomers. 10 In this work we show very good copolymerizability of MDO with VAc which is due to the similarity in monomer structures in terms of nucleophilic double bond and stability of growing radicals. We calculated Q (monomer reactivity) and e (monomer polarity) values for MDO using a well known Alfrey-Price equation.…”
Section: Resultsmentioning
confidence: 51%
See 3 more Smart Citations
“…9 Davis et al have reported copolymerization parameters for copolymerization of MDO with MMA at 40 C as r MDO ¼ 0:057 and r MMA ¼ 34:12 thereby showing the low tendency of cyclic ketene acetals to copolymerize with vinyl monomers. 10 In this work we show very good copolymerizability of MDO with VAc which is due to the similarity in monomer structures in terms of nucleophilic double bond and stability of growing radicals. We calculated Q (monomer reactivity) and e (monomer polarity) values for MDO using a well known Alfrey-Price equation.…”
Section: Resultsmentioning
confidence: 51%
“…is reported by us 11-18 and others. 10,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The main problem during the copolymerization is the huge reactivity difference between the CKA and the vinyl monomers leading to either low molecular weight homo vinyl polymers without ester linkages or copolymers incorporating only low amounts of the comonomers with block structure, incomplete ring-opening or no ring-opening at all.Keeping in view our broad aim of making new degradable materials with new properties based on the conventional plastics, here an attempt has been made to study the copolymerization behaviour of vinyl acetate (VAc) and MDO under conventional radical polymerization conditions. The resulting materials depending upon the glass transition temperatures could be proposed for further studies as degradable gums, coating materials, adhesives etc.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…MDOP also proceed with 100% ring opening for polymer and easily copolymerize with vinylic monomers such as styrene, N-isopropylacrylamide, methyl acrylate and methyl methacrylate, and so on using AIBN as a thermal radical initiator. [9][10][11][12] These resulting copolymers have degradable caprolactone (CL) units in their molecular backbones.…”
mentioning
confidence: 99%